Irrigation systems performance in Egypt - Allam M.N.; El Gamal F.; Hesham M. (Irrigation systems performance, 2005)
In Egypt the rainfall is rare and the desert covers most of the country area, except for a narrow strip of cultivated land and urban areas along the Nile river course. The quota of Egypt from the Nile River, which represents the main source of water of the country, hasn't changed since 1959. The Nile River in Egypt has supported the longest civilization over the world, which lasted more than seven thousands years. Egyptians, throughout the history, were skilful enough to efficiently utilize the Nile water. During this century, they installed an invaluable water structure; High Aswan Dam (HAD), which controlled the water releases pattern over the year. Nile river ends up with a unique delta region that extends over an area of about 6.0 million feddans of alluvial soils. Another batch of alluvial soils extends over about 2.5 million feddans along the Nile stem in the upstream. The Delta region is characterised with large tracts of rich fertile agricultural land, overpopulation, unique and delicate environmental conditions caused by the mixing of drainage and fresh water, unique flora and fauna, and problems associated with low lying areas such as sea water intrusion.
2. WASAMED Workshop: Irrigation Systems Performance, 2004/06/24-28, Hammamet (Tunisia)